2016
DOI: 10.1002/msc.1164
|View full text |Cite
|
Sign up to set email alerts
|

What impact does written information about fatigue have on patients with autoimmune rheumatic diseases? Findings from a qualitative study

Abstract: ObjectivesAlthough fatigue is a common symptom for people with rheumatic diseases, limited support is available. This study explored the impact of written information about fatigue, focusing on a booklet, Fatigue and arthritis.MethodsThirteen patients with rheumatic disease and fatigue were recruited purposively from a rheumatology outpatient service. They were interviewed before and after receiving the fatigue booklet. Two patients, plus six professionals with relevant interests, participated in a focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The usual care fatigue booklet18 in this RCT was written by the team following the original RCT 12. A qualitative study suggested that patients felt the booklet made them feel more responsible for taking actions to manage their fatigue 34. The brief booklet discussion with the nurse in this RCT may have had a greater effect than a patient picking up a booklet in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The usual care fatigue booklet18 in this RCT was written by the team following the original RCT 12. A qualitative study suggested that patients felt the booklet made them feel more responsible for taking actions to manage their fatigue 34. The brief booklet discussion with the nurse in this RCT may have had a greater effect than a patient picking up a booklet in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…31 The usual-care booklet, written after the first RCT and based on the results of that intervention, 45 has been available in rheumatology units since 2011 and was therefore used as a 'usual-care' active control in the present study. Although the booklet has never been subjected to rigorous effectiveness testing, a recent qualitative study 88 suggested that patients felt that it made them think differently about their fatigue. Patients in the study 88 reported that having a discussion of the booklet with a researcher made them consider taking responsibility for managing some aspects of their fatigue and try the suggestions the booklet contained.…”
Section: Discussionmentioning
confidence: 99%
“…Although the booklet has never been subjected to rigorous effectiveness testing, a recent qualitative study 88 suggested that patients felt that it made them think differently about their fatigue. Patients in the study 88 reported that having a discussion of the booklet with a researcher made them consider taking responsibility for managing some aspects of their fatigue and try the suggestions the booklet contained. Although the focus of the qualitative study was for patients to review the booklet for research, it raises the possibility that the brief booklet discussion with the health professional (usual care in this RCT) may have delivered an effect over and above a patient simply picking the booklet up from the clinic display.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the risk of nocebo effects in relation to our comparator did not appear substantial. As a minimum, participants in the usual care group received established educational materials, which have previously been associated with a positive impact 30 and, within this trial, were related to improved outcomes compared with the baseline score and equivalent attrition rates. Second, 12% of participants given PEP and CBA discontinued their respective therapies due to multiple reasons.…”
Section: Discussionmentioning
confidence: 99%